2005
DOI: 10.1111/j.1460-9568.2005.04166.x
|View full text |Cite
|
Sign up to set email alerts
|

Two‐way active avoidance training‐specific increases in phosphorylated cAMP response element‐binding protein in the dorsal hippocampus, amygdala, and hypothalamus

Abstract: Previous studies have demonstrated that the activation of pontine-wave (P-wave) generating cells in the brainstem during post-training rapid eye movement (REM) sleep is critical for the consolidation of memory for two-way active avoidance (TWAA) learning in the rat. Here, using immunocytochemistry, we investigated the spatio-temporal distribution of CREB phosphorylation within different parts of the dorsal hippocampus, amygdala, and hypothalamus following a session of TWAA training in the rat. We show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 81 publications
3
24
0
Order By: Relevance
“…Taken together, these data indicate that CREB activation in this subfield is required for spatial LTM formation. However, an induction of CREB phosphorylation in the CA3 region has been also reported after nonspatial learning (Saha and Datta 2005). In accord with the role of CREB signaling in CA3 region in LTM formation, a selective induction of c-fos in this CA3 region during the consolidation processes has previously been demonstrated (Bertaina-Anglade et al 2000; He et al 2002).…”
Section: Discussionsupporting
confidence: 48%
“…Taken together, these data indicate that CREB activation in this subfield is required for spatial LTM formation. However, an induction of CREB phosphorylation in the CA3 region has been also reported after nonspatial learning (Saha and Datta 2005). In accord with the role of CREB signaling in CA3 region in LTM formation, a selective induction of c-fos in this CA3 region during the consolidation processes has previously been demonstrated (Bertaina-Anglade et al 2000; He et al 2002).…”
Section: Discussionsupporting
confidence: 48%
“…We are aware of no studies examining IEG activation with Sidman AA, but several have examined signaled AA (Nikolaev et al 1992;Duncan et al 1996;Savonenko et al 1999;Radwanska et al 2002;Saha and Datta 2005). Unfortunately, the results fail to paint a clear picture of the AA neurocircuit.…”
Section: Discussionmentioning
confidence: 99%
“…One study also found elevated c-Fos in mPFC following AA training (Duncan et al 1996). However, most of these studies identified additional brain regions of presumably equal importance, such as the cingulate cortex, lateral septum, and various hypothalamic nuclei (Duncan et al 1996;Saha and Datta 2005), with little overlap between studies.…”
Section: Discussionmentioning
confidence: 99%
“…To assess postsynaptic BLA neuronal activity, we determined immunoreactivity for the phosphorylated form of the transcription factor cAMP response element-binding (pCREB) protein. Noradrenergic stimulation induces pCREB activation (32,33), and several findings have implicated CREB phosphorylation in the amygdala in the modulation of memory consolidation (33)(34)(35). One-way ANOVA for pCREB immunoreactivity in the BLA revealed a significant group effect (F 7,34 ϭ 5.58; P Ͻ 0.0005).…”
Section: Corticosterone Effects On Basolateral Amygdala Neuronal Actimentioning
confidence: 98%